REVIEW ON NEEM (AZADIRECTA INDICA A. JUSS.) AS A POTENTIAL SOURCE OF ORGANIC PESTICIDE - Archana, *Borokar; Tabassum, Pansare; Pranita, Dodke (International Journal of Ayurveda and Pharma Research, 2017)
Extensive usage of broad spectrum synthetic pesticides during the last century has created so many environmental problems worldwide, most of the pesticides and chemicals are not biodegradable and due to bioaccumulation can enters into food chain and affects human and animal health. To overcome such problems focus on the use of plant based pesticides is the need of time. Because of their easy biodegradation, least toxic to the non- target organisms, economic and easy availability popularity of such plant based pesticides increases day by day. Among the recognized pesticidal plants, the Neem tree Azadirachta indica A. Juss., belonging to the family meliaceae proved for numerous active ingredients of insecticidal and pesticidal properties. The active principle of Neem tree is azadirachtin, a nortriterpenoids, possesses broad spectrum activity at low use rates, and classical growth regulator activity and unique mode of action (ecdysone disruptor) make azadirachtin as an ideal candidate for insecticide resistance, integrated pest control and organic pest control programme. Neem products are effective against various pest of crop field such as whiteflies, leaf miners, fungus, aphids, and many leaf eating caterpillars and also in stored grains like rice, wheat, corn etc. This review gathered information related to the Neem tree as a better biopesticides and try to develop awareness about side effects of chemical pesticides and benefits of biopesticides among farmers, agricultural industry and in laymen.